(untitled) (Medico Legal Update, 2021)
Based on projections of the National Development Planning Agency (Bappenas) the number of population Indonesia in 2018 reached 265 million people. The number consists of 133,17 million men and 131,88 million women and 44,10 million are teenagers. The population data in South Sulawesi in 2018 was 8,771,970 people and in 2015 the population of South Sulawesi was 8,520 million people and 1,56 million people were teenagers. Adolescent sexual behavior, especially premarital sexual behavior, still dominates the debate in terms of moral, psychological, and physical. Premarital sex in adolescents is a serious problem because it relates to the low use of contraception and adolescents tend to have more sexual partners if they start having premarital sex at an earlier age. This article aims to find out knowledge, attitudes, actions of premarital sexual behavior and its relationship with the environment promiscuity in adolescents in Makassar, Indonesia. This research is an observational analytic study with cross-sectional study design. The time used in this study is 8 months. The location of the study will be conducted in high school students 17 & 19 in Makassar, one of the Metropolitan cities in Indonesia. The population in this study is high school students 17 & 19 in Makassar City as many as 200 students. In this study, researchers used the proportionate random sampling method, a sample consists of 134 students. The analysis used in the study was the Chi-Square test. This study results that there was a significant relationship between premarital sex knowledge with a social circle of friends with p-value = 0.029 and also a significant relationship between knowledge with a place to hang out with p-value = 0.009. There was a significant relationship between premarital sex attitudes with the social environment of friends with p-value = 0.034 and there was also a significant relationship between attitudes with the place to hang out with p-value = 0.020. There is a significant relationship between premarital sex behavior with the community’s social environment with p-value = 0.003.